Extracellular vesicles derived from Talaromyces marneffei contain immunogenic compounds and modulate THP-1 macrophage responses - Pruksaphon, Kritsada; Amsri, Artid; Thammasit, Patcharin; Nosanchuk, Joshua D.; Youngchim, Sirida (Frontiers in Immunology, 2023)
Pathogenic eukaryotes including fungi release extracellular vesicles (EVs) which are composed of a variety of bioactive components, including peptides, nucleic acids, polysaccharides, and membrane lipids. EVs contain virulence-associated molecules suggesting a crucial role of these structures in disease pathogenesis. EVs derived from the pathogenic yeast phase of Talaromyces (Penicillium) marneffei, a causative agent of systemic opportunistic mycoses “talaromycosis,” were studied for their immunogenic components and immunomodulatory properties. Some important virulence factors in EVs including fungal melanin and yeast phase specific mannoprotein were determined by immunoblotting. Furthermore, fluorescence microscopy revealed that T. marneffei EVs were internalized by THP-1 human macrophages. Co-incubation of T. marneffei EVs with THP-1 human macrophages resulted in increased levels of supernatant interleukin (IL)-1β, IL-6 and IL-10. The expression of THP-1 macrophage surface CD86 was significantly increased after exposed to T. marneffei EVs. These findings support the hypothesis that fungal EVs play an important role in macrophage “classical” M1 polarization. T. marneffei EVs preparations also increased phagocytosis, suggesting that EV components stimulate THP-1 macrophages to produce effective antimicrobial compounds. In addition, T. marneffei EVs stimulated THP-1 macrophages were more effective at killing T. marneffei conidia. These results indicate that T. marneffei EVs can potently manipulate macrophage functions, resulting in the activation of these innate immune cells to enhance their antimicrobial activity.